Melioidosis: acute respiratory distress syndrome and sepsis - Shah, Bharat M.; Patel, Jimit (International Journal of Research in Medical Sciences, 2024)
Melioidosis is a serious infection caused by the bacterium Burkholderia pseudomallei (B. pseudomallei) mostly found in endemic areas like Southeast Asia. Herein, we presented a case of melioidosis in a 32-year-old man who presented with respiratory distress, was a known case of type 2 diabetes not on any treatment presented to the emergency department (ED) with a history of pustules over skin, shortness of breath, and fever. He was initially misdiagnosed and treated as pulmonary tuberculosis in another hospital prior to his latest presentation. Melioidosis is a severe infection that can be misdiagnosed due to variable presentation and low awareness among healthcare workers of the disease. Diagnosis requires high clinical suspicion, especially in patients who are coming from endemic areas with appropriate risk factors such as diabetes mellitus. Treatment with appropriate antibiotics for a long duration, and outpatient follow-up is vital to reduce the risk of recurrence.